Se divertir dans Les Rougon-Macquart - Céline Grenaud-Tostain (Flaubert: Revue Critique et Génétique)
Divertissement, as it is presented in Les Rougon-Macquart, is based on a social will to live. It strives to ward off the unbearable vision of the human condition. It is therefore necessary to question the validity of an intertextuality in which Schopenhauer, Pascal and Montaigne manage to negotiate a privileged place. The poetics of divertissement is linked to a philosophy of life and death that calls for a decoding. Along the way, the aim is to thwart the caricature of an outrageous and highly reductive pessimism in Les Rougon-Macquart.